1991
DOI: 10.1007/bf02294584
|View full text |Cite
|
Sign up to set email alerts
|

Nonunique solutions to the likelihood equation for the three-parameter logistic model

Abstract: item response theory, maximum likelihood estimation, tests,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…These evaluations found that PARMATE produced item parameter estimates that were almost always slightly more accurate than those of both B1LOG and LOGIST. For a given set of item parameters, and in the absence of multiple maxima in the likelihood function (Yen, Burket, & Sykes, 1991), maximum likelihood trait estimates produced by PARMATE and LOGIST are identical.…”
Section: Scaling Proceduresmentioning
confidence: 99%
“…These evaluations found that PARMATE produced item parameter estimates that were almost always slightly more accurate than those of both B1LOG and LOGIST. For a given set of item parameters, and in the absence of multiple maxima in the likelihood function (Yen, Burket, & Sykes, 1991), maximum likelihood trait estimates produced by PARMATE and LOGIST are identical.…”
Section: Scaling Proceduresmentioning
confidence: 99%
“…Then, for any values of , we could expect the converged values, ( , , , , and ). We cannot always guarantee that the converged values are uniquely determined ( [13], [14]). However, we have experienced that the converged values are uniquely determined in many cases.…”
Section: Matrix Completion By Using the Em-type Irtmentioning
confidence: 99%
“…We cannot always guarantee that the converged values are uniquely determined ( [15], [16]). However, we have experienced that the converged values are uniquely determined in many cases.…”
Section: A Matrix Completion By Using the Em-type Irtmentioning
confidence: 99%